Time-course transcriptome analysis of lungs from mice exposed to ricin by intratracheal inoculation. (1st February 2021) - Jiao, Zhouguang; Li, Sha; Su, Duo; Gan, Changjiao; Zhao, Xiaodong; Gao, Bo; Qiu, Yefeng; Song, Yajun; Zhou, Dongsheng; Hu, Lingfei; Yang, Huiying
Highlights: Neutrophils infiltrated the lungs within 24 h of exposure to ricin. Gene Expression of leukocyte migration and inflammatory response increased. Expression of genes related to antioxidant activity decreased over the first 12 h. Atf3 and Egr1 may play crucial roles in ricin-induced lung damage. Abstract: In this study, a ricin toxin (RT)-induced pulmonary intoxication model was established in mice by intratracheal-delivered RT at a dose of 2× LD50 . Based on this model, the histopathological evaluation of the lungs at 24 h and 48 h post-exposure was executed, and the genome-wide transcriptome of the lungs at 4, 12, 24 and 48 h post-exposure was analyzed. Histopathological analysis showed that a large number of neutrophils infiltrated the lungs at 24 h post-exposure, and slight pulmonary edema and perivascular-peribronchiolar edema appeared in the lungs at 48 h. Transcriptome analysis showed that the expression of a large number of genes related to leukocyte migration and chemotaxis consistently increased in the lungs upon exposure to RT, and the expression of genes that participate in acute phase immune and/or inflammatory response, also increased within 12 h of exposure to RT, which could be confirmed by the measurement of cytokines, such as IL-1β, TNF-α and IL-6, in bronchoalveolar lavage fluid. While the expression of genes related to cellular components of the extracellular matrix and cell membrane integrity consistently decreased in the lungs, and the expression of genes related to antioxidant activity also decreased within the first 12 h. There are 17 differentially expressed genes (DEGs) that participate in ribotoxic stress response, endoplasmic reticulum stress response or immune response in the lungs at 4 h post-exposure. The expression of these DEGs was upregulated, and the number of these DEGs accounted for about 59 % of all DEGs at 4 h. The 17 DEGs may play an important role in the occurrence and development of inflammation. Notably, Atf3, Egr1, Gdf15 and Osm, which are poorly studied, may be important targets for the subsequent research of RT-induced pulmonary intoxication. This study provides new information and insights for RT-induced pulmonary intoxication, and it can provide a reference for the subsequent study of the toxicological mechanism and therapeutic approaches for RT-induced pulmonary intoxication.